1983
DOI: 10.1128/jvi.47.1.185-192.1983
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 2 glycoprotein gF and type 1 glycoprotein gC have related antigenic determinants

Abstract: The 104-S monoclonal antibody immunoprecipitated from herpes simplex virus type 2 (HSV-2)-infected cell extracts the 75,000-molecular-weight glycoprotein gF and its 65,000-molecular-weight precursor (pgF). The precursor pgF was sensitive to endoglycosidase H digestion, indicating the presence of high mannose-type oligosaccharides, whereas the stable gF product was sensitive to neuraminidase digestion, indicating the presence of sialic acid residues. The 104-S antibody also weakly precipitated the 130,000-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 38 publications
(37 reference statements)
4
39
0
Order By: Relevance
“…Antibodies that precipitated proteins of the heterotype virus were most readily detected in convalescent-phase sera: Antibodies to HSV-2 gB and p148 were detected in early sera from all patients with HSV-1 infections, and antibodies to HSV-1 p148, gC, and gB were detected in early sera from most HSV-2 patients (Table ID). The early human antibodies that recognize both HSV-1 and HSV-2 glycoprotein antigens are consistent with reports of type common epitopes on gB [Pereira et al, 19811 and also with the report of cross-reactivity and genetic relatedness of HSV-1 gC and one of the components of the HSV-2 g80 complex [Zweig et al, 1983;Zezulak et al, 19831. In summary, our data indicates that in both genital HSV-1 and HSV-2 infections, a sequential immune response to HSV-specific polypeptides can be identified. In both primary HSV-1 and HSV-2 infections precipitating antibodies to several glycosylated and nonglycosylated proteins appear early in the course of infection.…”
Section: Discussionsupporting
confidence: 81%
“…Antibodies that precipitated proteins of the heterotype virus were most readily detected in convalescent-phase sera: Antibodies to HSV-2 gB and p148 were detected in early sera from all patients with HSV-1 infections, and antibodies to HSV-1 p148, gC, and gB were detected in early sera from most HSV-2 patients (Table ID). The early human antibodies that recognize both HSV-1 and HSV-2 glycoprotein antigens are consistent with reports of type common epitopes on gB [Pereira et al, 19811 and also with the report of cross-reactivity and genetic relatedness of HSV-1 gC and one of the components of the HSV-2 g80 complex [Zweig et al, 1983;Zezulak et al, 19831. In summary, our data indicates that in both genital HSV-1 and HSV-2 infections, a sequential immune response to HSV-specific polypeptides can be identified. In both primary HSV-1 and HSV-2 infections precipitating antibodies to several glycosylated and nonglycosylated proteins appear early in the course of infection.…”
Section: Discussionsupporting
confidence: 81%
“…The immunological relatedness of HSVl and HSV2 can be demonstrated using the neutralizing activity of immune sera [Vestergaard, 19801; a correlate of typecommon neutralizing antibody at the molecular level is the fact that glycoproteins gB, and gD have type-common epitopes [Vestergaard, 19801. Glycoprotein gC in contrast, was until recently thought to have only serotype-specific epitopes. Two reports [Zweig et al, 1983;Zezulak et al, 19831, however, have suggested that this polypeptide may also have cross-reacting antigenic determinants. The identification of polypeptides with type-specific epitopes is becoming even more important as the use of monoclonal antibodies as diagnostic reagents increases.…”
Section: Discussionmentioning
confidence: 93%
“…The glycoproteins specified by these genes are quite different in size, however, in part because gC-1 contains a stretch of 27 amino acids near its NH2-terminus that are not present in gC-2 (26,27). Moreover, the number of antigenic determinants shared by the two glycoproteins seems to be limited in comparison with the unique antigenic determinants (14,19,28,29). Although these two homologous glycoproteins have diverged with time more than some of the other homologous HSV-1 and HSV-2 glycoproteins, it appears that they retain a common affinity for C3b and very likely also retain common activities associated with this binding activity .…”
Section: Identification Of C3-binding Proteins From Extracts Of Hsv-1mentioning
confidence: 99%